Development of mobile application framework based on competency-based education for technical and vocational education - Abdul Rahman, Khairul Anuar; Abd Jalil, Norazwani; M.Arsad, Mohd Azhar; Hashim, Suhaizal; Rahim, Mohd Bekri; Nur Yunus, Faizal Amin; Razali, Nizamuddin; Ismail, Mohd Erfy (Penerbit UTHM, 2021)
This study aimed to develop a mobile application framework based on Competency-Based Education (CBE) in Technical and Vocational Education. CBE approach in teaching and learning should be applied because this approach is suitable for skill-based education. In technological advancement, the mobile application approach causes students to have their own control in teaching and to learn to be implemented seamlessly and more effectively. This research is a qualitative method that has gone through three phases to form a framework for the mobile app based on CBE. The instruments used are structured interview and evaluators' reliability review form. The study sample consisted of 6 experts in CBE and technology for the interview session and 3 experts in TVET for reliability data verification. The raw data obtained from the interviews have gone through a thematic analysis process using Atlas.ti software. The results show 36 items identified as characteristics of CBE in the mobile application, with the average Cohen Kappa Index Approval coefficient was 0.9 indicating a very good reliability scale. The findings of this study consist of 33 items with seven constructs approved after the inter-rater reliability among the expert. The implication from this research could be used as guidance in the development of the instructional mobile application, particularly in Technical and Vocational Education and as an instrument for evaluating existing instructional mobile applications.